Repairing the Relationship between Students and Nature. Issue 1 (4th March 2019) - Roberts, Kean; Kruse, Jerrid
Abstract: As people seek out more naturalistic experiences (e.g. camping, visiting National and State Parks, etc.), it is increasingly important for students to leave our classrooms with an understanding of and relationship to nature. The NGSS exposes students to environmental problems of today and works toward the EPA's description of environmental literacy (2004). To help foster this relationship for students, we have explicit discussions with students about: (1) what nature is, (2) the benefits (e.g. justifications) for natural experiences, (3) how nature influences humans, (4) how humans impact nature, and (5) human responsibility to conserve and preserve nature. Through such discussions, our students begin demonstrating personal justifications for nature as well as a deeper relationship to the natural world. Students recognize the importance of protecting the health of natural resources while taking or using only what is necessary for their consumption, and become responsible consumers. Most importantly, we want to prepare our students to be better natural stewards.